Field-grown transgenic wheat expressing the sunflower gene HaHB4 significantly outyields the wild type - Gonzalez, Fernanda Gabriela; Capella, Matías; Ribichich, Karina Fabiana; Curín, Facundo; Giacomelli, Jorge Ignacio; Ayala, Francisco; Watson, Gerónimo; Otegui, María Elena; Lía Chan, Raquel (2019)
HaHB4 is a sunflower transcription factor belonging to the homeodomain-leucine zipper I family whose ectopic expression in Arabidopsis triggers drought tolerance. The use of PCR to clone the HaHB4 coding sequence for wheat transformation caused unprogrammed mutations producing subtle differences in its activation ability in yeast. Transgenic wheat plants carrying a mutated version of HaHB4 were tested in 37 field experiments. A selected transgenic line yielded 6% more (P<0.001) and had 9.4% larger water use efficiency (P<0.02) than its control across the evaluated environments. Differences in grain yield between cultivars were explained by the 8% improvement in grain number per square meter (P<0.0001), and were more pronounced in stress (16% benefit) than in non-stress conditions (3% benefit), reaching a maximum of 97% in one of the driest environments. Increased grain number per square meter of transgenic plants was accompanied by positive trends in spikelet numbers per spike, tillers per plant, and fertile florets per plant. The gene transcripts associated with abiotic stress showed that HaHB4’s action was not dependent on the response triggered either by RD19 or by DREB1a, traditional candidates related to water deficit responses. HaHB4 enabled wheat to show some of the benefits of a species highly adapted to water scarcity, especially in marginal regions characterized by frequent droughts.